Dora and the lost city of gold [videorecording (DVD)] - Merced, Isabela, 2001-; Derbez, Eugenio; Peña, Michael, 1976-; Longoria, Eva, 1975- (Paramount, 2019)
Having spent most of her life exploring the jungle with her parents, nothing could prepare Dora for her biggest challenge yet: High School. When her parents mysteriously disappear while searching for the Lost City of Gold, Dora must swing into action and lead a group of ill-equipped high schoolers on a quest to save them. It is a high stakes mission as Dora and her new friends navigate the jungle, outrun treasure hunters and solve ancient puzzles to unlock the mystery of the fabled city.